FIXED POINT THEOREM ON Lp AS 2-NORMED SPACES - EKARIANI (NIM : 20110002), SHELVI
In (4), Gunawans showed that the space Lp of p-summable sequences can be equipped with the 2-norm. In this thesis we shall study about the equivalence. This result is used to prove a Fixed Point Theorem which is more general than the Fixed Point Theorem in (4).